Effect of gradual adjustment of surgical position in prevention of complications of thyroid surgery - SUN, Yahong; LIN, Juan; HOU, Zhinan (Chinese Journal of Integrative Nursing, 2023)
Objective To investigate the effect of gradual adjustment of surgical position in prevention of complications of thyroid surgery. Methods Totally 100 patients undergoing surgical treatment for thyroid diseases were divided into the control group and observation group, with 50 cases in each group. Conventional surgical position was in the control group, while the surgical position was gradually adjusted in the observation group. The incidence of postoperative complications and patient satisfaction with nursing service were measured and compared between two groups. Results The incidence rats of postural syndrome, circulatory complications, muscle tissue complications and ocular complications in the observation group were lower than those in the control group(P＜0. 05). The scores of service attitude assessment and patient satisfaction assessment in the s in the observation group were higher than those in the control group(P＜0. 05). Conclusion Gradual adjustment of surgical position is potentially effective to reduce the postoperative complications of thyroid surgery and improve the quality of surgical nursing. (目的 探究渐进式体位在降低甲状腺手术并发症中的应用效果。方法 选取2022年7月—12月医院收治的甲状腺疾病行手术治疗的100例患者为研究对象, 分为对照组和观察组, 各50例。对照组采用常规手术方式和手术体位, 观察组基于常规术式及体位的基础上进行渐进式体位调整。对比两组术后并发症发生和患者对围手术期护理的评价。结果 观察组术后体位综合征、循环系统并发症、肌肉组织并发症和眼部并发症发生率均低于对照组, 差异有统计学意义(P＜0. 05)。观察组患者服务态度评分和护理满意度评分均高于对照组(P＜0. 05)。结论 运用渐进式体位变换改良传统甲状腺手术体位, 可以降低术后并发症的发生率, 有利于优化甲状腺手术护理工作, 提升手术治疗质量。)